2008
DOI: 10.1091/mbc.e07-10-1089
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-coupled Receptor-promoted Trafficking of Gβ1γ2Leads to AKT Activation at Endosomes via a Mechanism Mediated by Gβ1γ2-Rab11a Interaction

Abstract: G-protein coupled receptors activate heterotrimeric G proteins at the plasma membrane in which most of their effectors are intrinsically located or transiently associated as the external signal is being transduced. This paradigm has been extended to the intracellular compartments by studies in yeast showing that trafficking of G␣ activates phosphatidylinositol 3-kinase (PI3K) at endosomal compartments, suggesting that vesicle trafficking regulates potential actions of G␣ and possibly G␤␥ at the level of endoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 75 publications
1
48
0
Order By: Relevance
“…Association of heterotrimeric G protein components with endosomal compartments has been observed in mammalian cells in the context of their function in receptor-mediated signaling Garcia-Regalado et al, 2008;Hynes et al, 2004;Saini et al, 2007). Our work demonstrates that heterotrimeric G protein subunits are also very dynamic in the context of their role in asymmetric cell division, which is thought to be receptor independent (for reviews, see Gönczy, 2008;Knoblich, 2008).…”
Section: Gb Trafficking In Early C Elegans Embryosmentioning
confidence: 52%
“…Association of heterotrimeric G protein components with endosomal compartments has been observed in mammalian cells in the context of their function in receptor-mediated signaling Garcia-Regalado et al, 2008;Hynes et al, 2004;Saini et al, 2007). Our work demonstrates that heterotrimeric G protein subunits are also very dynamic in the context of their role in asymmetric cell division, which is thought to be receptor independent (for reviews, see Gönczy, 2008;Knoblich, 2008).…”
Section: Gb Trafficking In Early C Elegans Embryosmentioning
confidence: 52%
“…More specifically, lipid rafts have been implicated as a domain where PKC-␣-dependent phosphorylation of Akt occurs (24). Other investigators, however, reported evidence indicating that in some signaling pathways, endocytosis is required for Akt activation (15,26,53). For example, the APPL1 protein, a marker of APPL endosomes (precursors of EEA1 early endosomes (16)), is required for Akt phosphorylation in zebrafish (15).…”
Section: Discussionmentioning
confidence: 99%
“…In the conventional model, Akt activation mainly occurs at the plasma membrane in lipid rafts and nonlipid raft microdomains (23,24). We and others (15,(25)(26)(27)(28) reported that general inhibitors of endocytosis and/or intracellular membrane trafficking modulate signaling events initiated at the plasma membrane. For example, a dynamin dominant negative mutant, concanavalin A and methyl-␤-cyclodextrin prevent Akt activation in several cell types (27,29).…”
mentioning
confidence: 99%
“…Rab11 controls movement of proteins through a recycling compartment that forms via processing of early endosomes and mediates movement of endocytosed proteins back to the plasma membrane (48,49). S25N Rab11 disrupts this process and impairs both processing of and signaling via G-protein-coupled receptors, including the lysophosphatidic acid receptor (48,50). Both S34N Rab5 and S25N Rab11 profoundly impaired the ability of TNF-␣ (Fig.…”
Section: In Vsm Cells Tnf-␣ Activates CLmentioning
confidence: 99%